Аналіз зарубіжного досвіду адміністративно-правового регулювання захисту прав платників податків - Литвинов, Сергій Валентинович; Литвинов, Сергей Валентинович; Litvinov, Sergej (Одеса : Юрид. л-ра, 2014)
The article deals with the research of the administrative and legal regulation of taxation. Functionally integral approach to this field that provides the determination of its goals, general functional structure, functional roles of its subjects, goal-directed understanding of the functions of the taxation legal relationships subjects in foreign countries was suggested.
Литвинов С. В. Аналіз зарубіжного досвіду адміністративно-правового регулювання захисту прав платників податків / С. В. Литвинов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 189-194.
Keywords: податкові правовідносини; податкове законодавство; податок; платник податків; структура податкових правовідносин; налоговые правоотношения; налоговое законодательство; налог; налогоплательщик; структура налоговых правоотношений; tax legal relationship; tax legislation; tax; taxpayer; structure of tax legal relations